Antibody-dependent enhancement of severe dengue disease in humans - Katzelnick, Leah C.; Gresh, Lionel; Halloran, M. Elizabeth; Mercado, Juan Carlos; Kuan, Guillermina; Gordon, Aubree; Balmaseda, Angel; Harris, Eva (Science (American Association for the Advancement of Science), 2017)
For dengue viruses 1 to 4 (DENV1-4), a specific range of antibody titer has been shown to enhance viral replication in vitro and severe disease in animal models. Although suspected, such antibody-dependent enhancement of severe disease has not been shown to occur in humans. Using multiple statistical approaches to study a long-term pediatric cohort in Nicaragua, we show that risk of severe dengue disease is highest within a narrow range of preexisting anti-DENV antibody titers. By contrast, we observe protection from all symptomatic dengue disease at high antibody titers. Thus, immune correlates of severe dengue must be evaluated separately from correlates of protection against symptomatic disease. These results have implications for studies of dengue pathogenesis and for vaccine development, because enhancement, not just lack of protection, is of concern.